2010
DOI: 10.1016/j.bbmt.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Donor KIR Genes 2DL5A, 2DS1 and 3DS1 Are Associated with a Reduced Rate of Leukemia Relapse After HLA-Identical Sibling Stem Cell Transplantation for Acute Myeloid Leukemia but Not Other Hematologic Malignancies

Abstract: Stem cell transplantation (SCT) from a healthy donor can be curative for patients with hematologic malignancies resistant to other treatments. Elimination of malignant cells through a graft-versus-leukemia (GVL) effect involves donor T and natural killer (NK) cells, but their relative contribution to this process is poorly defined. NK cell alloreactivity and GVL effects are controlled by the nature of the interaction of NK activation receptors and killer-immunoglobulin-like-receptors (KIR) with major histocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 23 publications
6
45
0
2
Order By: Relevance
“…In spite of this combination, one of the two relapsed with the other patient dying early due to transplant-related complications. Recently, Stringaris et al 38 noted that patients undergoing T-cell-depleted HLA-identical HSCT for AML from donors with all three of KIR2DL5A, KIR2DS1 and KIR3DS1 had a significantly lower relapse rate compared with patients whose donors did not have this combination. This explanation cannot be used to explain our results as the only patient in out cohort who had this combination of KIR genes was the only patient in our cohort who died of relapsed AML, and none of the three long-term survivors had this combination.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this combination, one of the two relapsed with the other patient dying early due to transplant-related complications. Recently, Stringaris et al 38 noted that patients undergoing T-cell-depleted HLA-identical HSCT for AML from donors with all three of KIR2DL5A, KIR2DS1 and KIR3DS1 had a significantly lower relapse rate compared with patients whose donors did not have this combination. This explanation cannot be used to explain our results as the only patient in out cohort who had this combination of KIR genes was the only patient in our cohort who died of relapsed AML, and none of the three long-term survivors had this combination.…”
Section: Discussionmentioning
confidence: 99%
“…21 The benefit of donor KIR B haplotypes also has been observed for T cell-replete transplants from HLAmatched sibling donors, 47 an effect reported in other settings. 22,23 The authors of numerous other studies have reported varied effects of activating KIR on outcomes after various types of HCT, including increased rates of acute GVHD, 25,48,49 or protection against acute GVHD. 50 KIR B haplotypes are present in two-thirds of unrelated donors.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similar effects have been reported by other investigators in unrelated donor and sibling donor settings. 22,23 Because KIR B haplotypes are present in approximately two-thirds of unrelated registry donors, interventions that merely increase the probability of selecting KIR B donors are unlikely to affect survival because most donors already have this characteristic by chance. Further, the specific genetic mechanism for the protective effect of B haplotype donors, perhaps attributable to the presence or absence of individual or groups of inhibitory or activating KIR, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In adult patients, it has been reported that most acute myeloid leukemia (AML), 14 but only a minority of ALL cells, are susceptible to NK-cell mediated lysis. 15,16 On the contrary, recent studies of high-risk pediatric ALL undergoing haploidentical HSCT have highlighted the importance of choosing donors with alloreactive NK cells 17,18 to successfully cure these patients. The biological reasons responsible for the different susceptibility of adult and pediatric ALL blasts to the lytic effect played by alloreactive NK cells are so far still unknown.…”
Section: Introductionmentioning
confidence: 99%